Answer:
x = 14/3 + sqrt(217)/3 or x = 14/3 - sqrt(217)/3
Explanation:
Solve for x:
x + 4 + 1/x = (10 x)/7
Bring x + 4 + 1/x together using the common denominator x:
(x^2 + 4 x + 1)/x = (10 x)/7
Cross multiply:
7 (x^2 + 4 x + 1) = 10 x^2
Expand out terms of the left hand side:
7 x^2 + 28 x + 7 = 10 x^2
Subtract 10 x^2 from both sides:
-3 x^2 + 28 x + 7 = 0
Divide both sides by -3:
x^2 - (28 x)/3 - 7/3 = 0
Add 7/3 to both sides:
x^2 - (28 x)/3 = 7/3
Add 196/9 to both sides:
x^2 - (28 x)/3 + 196/9 = 217/9
Write the left hand side as a square:
(x - 14/3)^2 = 217/9
Take the square root of both sides:
x - 14/3 = sqrt(217)/3 or x - 14/3 = -sqrt(217)/3
Add 14/3 to both sides:
x = 14/3 + sqrt(217)/3 or x - 14/3 = -sqrt(217)/3
Add 14/3 to both sides:
Answer: x = 14/3 + sqrt(217)/3 or x = 14/3 - sqrt(217)/3